2012
DOI: 10.1007/s10554-012-0120-7
|View full text |Cite
|
Sign up to set email alerts
|

Left and right ventricular strain and strain rate measurement in normal adults using velocity vector imaging: an assessment of reference values and intersystem agreement

Abstract: Velocity vector imaging (VVI) software permits quantitative assessment of ventricular function through measurement of myocardial strain (S) and strain rate (SR). The purpose of this study was to define a reference range of ventricular S and SR values in normal adults using VVI software, and to describe the variability among observers and systems. Two-dimensional echocardiography was performed in 186 healthy adults free of cardiovascular disease or risk factors, followed by comprehensive ventricular S and SR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 38 publications
10
66
3
1
Order By: Relevance
“…26,33 However, it is significantly higher than what was reported in a study of healthy individuals free of cardiovascular disease, where, similar to the current study, only VVI software was utilized (−17.3%). 34 That study also demonstrated that LV-GLS values obtained using VVI software were similar for different echocardiography vendors (similar to our study). 34 However, a recent study has demonstrated that although there is a very strong correlation between LV-GLS values obtained using different strain analysis packages in same individuals, the absolute mean values vary between −18% and −21.5% (with a mean of −20% for the Siemens strain software).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…26,33 However, it is significantly higher than what was reported in a study of healthy individuals free of cardiovascular disease, where, similar to the current study, only VVI software was utilized (−17.3%). 34 That study also demonstrated that LV-GLS values obtained using VVI software were similar for different echocardiography vendors (similar to our study). 34 However, a recent study has demonstrated that although there is a very strong correlation between LV-GLS values obtained using different strain analysis packages in same individuals, the absolute mean values vary between −18% and −21.5% (with a mean of −20% for the Siemens strain software).…”
Section: Discussionsupporting
confidence: 90%
“…34 That study also demonstrated that LV-GLS values obtained using VVI software were similar for different echocardiography vendors (similar to our study). 34 However, a recent study has demonstrated that although there is a very strong correlation between LV-GLS values obtained using different strain analysis packages in same individuals, the absolute mean values vary between −18% and −21.5% (with a mean of −20% for the Siemens strain software). 35 However, that study included patients with a wide spectrum of LV systolic function, rather than healthy individuals free of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 90%
“…The relation of longitudinal strain with demographic factors has been previously described for RV, as well as for the other cardiac chambers. 15,19,24,30 This is the first study reporting the relationship between RVLS and 3D echocardiographic parameters of RV, LV, and RA size and function. Interestingly, both LV and RA longitudinal strain were identified as correlates of RVLS at multivariable analysis (RVLS increased in magnitude with the increase of both RALS and RVLS), suggesting the capability of 2DSTE to evaluate the functional coupling between RV-RA and RV-LV in the healthy heart.…”
Section: Segmental Variability Of Rv Strainmentioning
confidence: 94%
“…9 Seven studies included in this meta-analysis had small sample sizes (n=21-116) and used the EchoPac software, whereas only 1 larger study (n=186) used the VVI software. 24 As a consequence, the pooled reference values of RVLS were weighted by the significantly lower reference values of the latter (−21.7±4.2% for free wall RVLS by VVI software). Finally, several studies included in the meta-analysis used the conventional 4-chamber view for RVLS measurement and not the dedicated RV-focused view, the latter allowing a better definition of the RV free wall.…”
Section: Reference Values For Rv Strainmentioning
confidence: 99%
“…16,20,21 Table 2 summarizes normative values for the measures of function of the right side of the heart, and Figure 2 illustrates some of these measures. 16,[22][23][24][25][26][27][28][29][30][31] As discussed in the following paragraphs, myocardial deformation imaging is also emerging as a useful modality for imaging the right side of the heart. Several pearls are important in evaluating the cardiopulmonary unit by echocardiography.…”
Section: Overview Of Echocardiographic Evaluationmentioning
confidence: 99%